Valve replacement for Brucella endocarditis: two case reports. - Koumallos, N; Paschalis, A; Antoniades, C; Tousoulis, D; Simpsiris, P; Tolios, I; Stefanadis, C; Leonidas, D (2008)
We report two cases of successful treatment of Brucella endocarditis. Both of them were treated with antibiotics and aortic valve replacement after Brucellosis was diagnosed. In one of these cases emergency operation was required. Our observations suggest that a combined surgical and medical treatment is the best option for the management of this disease. B. endocarditis should be operated after improvement of clinical status but emergency cardiac surgery may be required if heart failure develops.